First-principles study of electron dynamics with explicit treatment of momentum dispersion on Si nanowires along different directions. (2nd September 2019) - Fatima,; Vogel, Dayton J.; Han, Yulun; Inerbaev, Talgat M.; Oncel, Nuri; Kilin, Dmitri S.
ABSTRACT: In this research, ground-state electronic structure and optical properties along with photoinduced electron dynamics of Si nanowires oriented in various directions are reviewed. These nanowires are significant functional units of future nano-electronic devices. All observables are computed for a distribution of wave vectors at ambient temperature. Optical properties are computed under the approximation of momentum conservation. The total absorption is composed of partial contributions from fixed values of momentum. The on-the-fly non-adiabatic couplings obtained along the ab initio molecular dynamics nuclear trajectories are used as parameters for Redfield density matrix equation of motion. The main outcomes of this study are transition energies, light absorption spectra, electron and hole relaxation rates, and electron transport properties. The results of these calculations would contribute to the understanding of the mechanism of electron transfer process on the Si nanowires for optoelectronic applications. GRAPHICAL ABSTRACT: